Modulation of gut microbiota and fecal metabolites by corn silk among high-fat diet-induced hypercholesterolemia mice - Ding, Lin; Ren, Shan; Song, Yaoxin; Zang, Chuangang; Liu, Yuchao; Guo, Hao; Yang, Wenqing; Guan, Hong; Liu, Jicheng (Frontiers in Nutrition, 2022)
Corn silk (CS) is known to reduce cholesterol levels, but its underlying mechanisms remain elusive concerning the gut microbiota and metabolites. The aim of our work was to explore how altered gut microbiota composition and metabolite profile are influenced by CS intervention in mice using integrated 16S ribosomal RNA (rRNA) sequencing and an untargeted metabolomics methodology. The C57BL/6J mice were fed a normal control diet, a high-fat diet (HFD), and HFD supplemented with the aqueous extract of CS (80 mg/mL) for eight weeks. HFD-induced chronic inflammation damage is alleviated by CS extract intervention and also resulted in a reduction in body weight, daily energy intake as well as serum and hepatic total cholesterol (TC) levels. In addition, CS extract altered gut microbial composition and regulated specific genera viz. Allobaculum, Turicibacter, Romboutsia, Streptococcus, Sporobacter, Christensenella, ClostridiumXVIII, and Rikenella. Using Spearman's correlation analysis, we determined that Turicibacter and Rikenella were negatively correlated with hypercholesterolemia-related parameters. Fecal metabolomics analysis revealed that CS extract influences multiple metabolic pathways like histidine metabolism-related metabolites (urocanic acid, methylimidazole acetaldehyde, and methiodimethylimidazoleacetic acid), sphingolipid metabolism-related metabolites (sphinganine, 3-dehydrosphinganine, sphingosine), and some bile acids biosynthesis-related metabolites including chenodeoxycholic acid (CDCA), lithocholic acid (LCA), ursodeoxycholic acid (UDCA), and glycoursodeoxycholic acid (GUDCA). As a whole, the present study indicates that the modifications in the gut microbiota and subsequent host bile acid metabolism may be a potential mechanism for the antihypercholesterolemic effects of CS extract.